FORMATION OF SPIRITUAL AND MORAL QUALITIES OF FUTURE TEACHERS - Tashmetova Shakhla Khusanovna (American Journals, 2023)
Training future teachers is an important task of the field of pedagogy. This article talks about the theoretical foundations of the formation of spiritual and moral qualities of future teachers.
Keywords: patriotism, humanitarianism, high morality, hard work, method.